The problem of tobacco smoking among high school students under the survey research - Gromysz-Kałkowska, Kazimiera; Unkiewicz-Winiarczyk, Aneta; Szubartowska, Ewa (Polish Journal of Public Health, 2011)
Introduction. Cigarette smoking by adolescents is still an ongoing problem exerting serious health effects. Despite numerous anti-tobacco campaigns, a great number of new victims fall into the habit.Aim. The problem undertaken in this study was to investigate the scale of smoking among students and comparison of the results obtained to the results of our previous survey research performed among children and teenagers in the same region of Poland. We also aimed at comparing our results to those obtained by other authors in higher education institutions in various regions of the country. Likewise in the other age groups, university students were asked the same questions referring to 9 thematic sections including factors that may prompt taking up the habit, the smoking initiation period, the circumstances of smoking and the number of cigarettes smoked daily, the causes of beginning and giving up smoking, and the level of knowledge about the hazardous effects of smoking.Material and method. The study involved 344 men and 487 women from the south-east of Poland who were aged 20-25 and studied at universities in Lublin. An anonymous questionnaire with questions concerning the above-mentioned issues was designed.Results. The student survey revealed 34.9% of smoking men and 26.9% of women smokers. The initiation of smoking took place at the age of 5-23. The largest number of students started smoking at the age 13-18. It was also found that the highest proportion of smoking students (irrespective of gender) came from the countryside. A very high percentage of smokers included students whose both parents smoked and when the parents were manual workers. The highest percent of students smoke when in company. As for the number of cigarettes smoked daily, it was reported that several percent of the students smoked up to 5 cigarettes a day, and less than 5% - more than 20 cigarettes per day. 10-20% of the students surveyed smoked up to 20 cigarettes daily. Illness and pregnancy in the case of women students strongly motivated to give up the habit.Conclusions. 1. The example set by smoking friends turned out to play the greatest role in initiation of the habit. However, at the time of study it is the stress associated with that period of students’ lives. 2. Cigarette smoking by students is largely determined by socio-economic factors. 3. Continuation of smoking is primarily related to social reasons. 4. The individuals surveyed exhibited full awareness of the dangers of smoking. Profound knowledge has the greatest impact on the decision to quit the habit.